2005
DOI: 10.1002/elps.200500169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metals on herbicides–α‐synuclein association: A possible factor in neurodegenerative disease studied by capillary electrophoresis

Abstract: The aggregation of alpha-synuclein in the dopaminergic neurons of the substantia nigra is a critical step in the Parkinson's disease (PD). The etiology of the disease is unknown but recent epidemiological and experimental studies have renewed interest in the hypothesis that environmental factors, especially herbicides and metals, have a role on the pathogenesis of PD. For the first time, the association constants of alpha-synuclein with five herbicides have been calculated using a capillary electrophoresis (CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…The simplest mechanism proposed involves a direct effect of the metal ions on the aggregation of the target proteins linked to these diseases. The effects reported for Zn 2+ ions on AS fibrillation revealed that metal concentrations in the mM range, far greater than those normally occurring in tissues, are necessary to accelerate the amyloid aggregation of the protein [67,68,[72][73][74][75], which argue against the physiological relevance that these effects might have on the etiology of the disease. Furthermore, no structural characterization of the Zn 2+ binding sites, or the identification of the amino acids involved in the metal-AS interactions has been reported to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplest mechanism proposed involves a direct effect of the metal ions on the aggregation of the target proteins linked to these diseases. The effects reported for Zn 2+ ions on AS fibrillation revealed that metal concentrations in the mM range, far greater than those normally occurring in tissues, are necessary to accelerate the amyloid aggregation of the protein [67,68,[72][73][74][75], which argue against the physiological relevance that these effects might have on the etiology of the disease. Furthermore, no structural characterization of the Zn 2+ binding sites, or the identification of the amino acids involved in the metal-AS interactions has been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, despite of the reported evidences that link Zn 2+ with the pathophysiology of PD and the fact that this metal ion was shown to promote AS fibrillation in vitro [67,68,[72][73][74][75], neither the structural characterization of the binding sites nor the identification of the amino acids involved in the interaction of Zn 2+ with the protein AS have been carried out. Accordingly, in this work we sought to delineate the structural basis behind the interaction of Zn 2+ with AS, as a first step towards the understanding of the molecular mechanism by which Zn 2+ accelerates AS filament assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of sporadic PD are considered to be idiopathic, but it is generally believed that the disease is a result of unknown environmental factors [49]. Recent evidence has suggested that some of these cases may be related to the exposure to environmental factors including heavy metals and pesticides [50,51]. Exposure to such factors could have significant effects on a-Syn regulation by both barriers and possibly contribute to PD pathology.…”
Section: Reviewmentioning
confidence: 99%
“…Do pesticides remain bound to α-synuclein once misfolding and fibrillation is triggered? Biophysical studies are essential to address these questions [85,86,87,88,89]. …”
Section: Introductionmentioning
confidence: 99%